Cognitive Load Theory for the Design of Medical Simulations. Issue 5 (October 2015) - Fraser, Kristin L.; Ayres, Paul; Sweller, John
Abstract : Summary Statement: Simulation-based education (SBE) has emerged as an effective and important tool for medical educators, but research about how to optimize training with simulators is in its infancy. It is often difficult to generalize results from experiments on instructional design issues in simulation because of the heterogeneity of learner groups, teaching methods, and rapidly changing technologies. We have found that cognitive load theory is highly relevant to teaching in the simulation laboratory and a useful conceptual framework to reference when designing or researching simulation-based education. Herein, we briefly describe cognitive load theory, its grounding in our current understanding of cognitive architecture, and the evidence supporting it. We focus our discussion on a few well-established cognitive load effects with examples from simulation training and recommend some instructional applications with theoretical potential to improve learning outcomes.